2016
DOI: 10.11646/zootaxa.4127.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of six Rhynchospio Hartman, 1936 species (Annelida: Spionidae) with comments on the evolution of brooding within the group

Abstract: Rhynchospio Hartman, 1936 is a small group of spionid polychaetes currently comprising ten described species distributed mainly in the Pacific. Five species examined to date are hermaphrodites producing spermatozoa with long nuclei, oocytes with thin and smooth envelopes, and dorsally brooding their offspring. Since our first molecular analysis of four Rhynchospio species, we have collected additional material from Northern Territory, Australia, and Oregon, USA. Herein, we describe the gamete and adult morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…cf. foliosa have been recorded, molecular data are only available for seven species (Radashevsky et al, 2014(Radashevsky et al, , 2016aSimon et al, 2019b; this study), and the phylogenetic placements of the other six species (i.e., R . asiatica , R .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cf. foliosa have been recorded, molecular data are only available for seven species (Radashevsky et al, 2014(Radashevsky et al, , 2016aSimon et al, 2019b; this study), and the phylogenetic placements of the other six species (i.e., R . asiatica , R .…”
Section: Discussionmentioning
confidence: 99%
“…Types of larval development (i.e., Pla: planktotrophic; Lec: lecithotrophic; and Dir: direct development). The morphological groups were created by the authors in this study and the other groups mentioned here were present on diff erent studies (Jamieson and Rouse, 1989;Blake and Arnofsky, 1999;Radashevsky et al, 2016aRadashevsky et al, , 2018Blake et al, 2020). 2).…”
Section: Morphological and Reproductive Characteristics Of Spionidsmentioning
confidence: 99%
“…To date, three Rhynchospio species, R. foliosa Imajima, 1991, R. gutaea (Ehlers, 1987, and R. tuberculata Imajima, 1991, have been recorded from Japan (Imajima 1991a). However, extensive morphological and molecular studies revealed the absence of records of R. glutaea from the northern Pacific Ocean (Radashevsky 2007;Radashevsky et al 2014Radashevsky et al , 2016a. Radashevsky et al (2014) also referred to R. arenicola Hartman, 1936, R. asiatica Chlebovisch, 1959, R. aff.…”
Section: Rhynchospio Aff Asiatica Sensu Radashevsky Et Al 2014 Figmentioning
confidence: 99%
“…We used the set of genes originally chosen for phylogenetic analysis of Spionidae [ 27 , 81 ]. The 16S rDNA is the most variable among examined markers and has been proven to be highly suitable for molecular identification at the species level for spionids [ 26 , 27 , 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used the set of genes originally chosen for phylogenetic analysis of Spionidae [ 27 , 81 ]. The 16S rDNA is the most variable among examined markers and has been proven to be highly suitable for molecular identification at the species level for spionids [ 26 , 27 , 81 , 82 , 83 , 84 , 85 , 86 ]. Our genetic analysis of 16S dataset, however, does not reveal strongly robust biogeographic patterns of P. hoplura populations worldwide, since haplotype analysis was not the primary objective of our study, nor were our analyzed sample sizes large enough to reveal the full extent of haplotype diversity in any one region.…”
Section: Discussionmentioning
confidence: 99%